IMPROVING MATHEMATICS ACHIEVEMENT OF INDONESIAN 5TH GRADE STUDENTS THROUGH GUIDED DISCOVERY LEARNING - Yurniwati Yurniwati; Latipa Hanum (Journal on Mathematics Education, 2017)
This research aims to find information about the improvement of mathematics achievement of grade five student through guided discovery learning. This research method is classroom action research using Kemmis and Taggart model consists of three cycles. Data used in this study is learning process and learning results. Learning process data is obtained by check list and is descriptive analyzed. Learning results data is obtained by conducting test and is analyzed by simple statistics. The result shows that student's ability of observation, discussion and knowledge acquisition are improved with guided discovery learning. Hence, guided discovery learning improves studentsâ€™ mathematics learning outcomes. Keywords: Mathematics Achievement, Guided Discovery LearningÂ DOI: http://dx.doi.org/10.22342/jme.8.1.3209.77-84